Nicotine-free vape liquids containing essential oils of peppermint, lavender, and tangerine: safety and efficacy profiles - Prasetya, Rahmad Aji; Arifiyana, Djamilah; Syulthoni, Zain Budi (Universitas Ahmad Dahlan, 2024)
Despite low nicotine levels, cigarettes and vape liquids can cause addiction, which makes quitting smoking difficult owing to withdrawal syndrome. Hence, we created a nicotine-free liquid vape using essential oils (EOs) like peppermint (Mentha piperita), lavender (Lavandula latifolia), and tangerine (Citrus reticulata) to substitute the nicotine in inducing relaxation without addiction. Thus, this study aimed to examine (1) the safety profile of this nicotine-free liquid vape by observing chemical characteristics using gas chromatography-mass spectrometry (GC-MS) and (2) its efficacy in reducing short-term anxiety in healthy volunteers who had previously used nicotine vape. The most complicated vape liquid formula (F4), containing propylene glycol, vegetable glycerin, with those three EOs, was injected into GC-MS, and the mass spectra were compared to the Wiley mass spectral library to identify the compound name. For the efficacy test, subjects who met inclusion criteria and fulfilled informed consent were randomly assigned to five groups (four groups received test liquids formula (F1-F4) while one group received placebo). Before and after using the vape liquid, subjects were asked to complete the State-Trait Anxiety Inventory (STAI) questionnaire to assess its anxiety-reduction effects. The result showed that nicotine-free vape liquids containing three EOs did not show any foreign substances that had never been encountered before, which means our product is safer than nicotine-containing vape liquids. This safety was also supported by all study subjects who did not report any adverse effects. The efficacy test showed that subjects who used vape liquids with essential oils (F1-F4) experienced a significant decrease in heart rate and systolic blood pressure. At the same time, 50% had a lower post-test STAI score, indicating a decrease in anxiety, although it was not statistically significant.